The association of immediate post cardiac arrest diastolic hypertension and survival following pediatric cardiac arrest. (August 2019) - Topjian, Alexis A.; Sutton, Robert M.; Reeder, Ron W.; Telford, Russell; Meert, Kathleen L.; Yates, Andrew R.; Morgan, Ryan W.; Berger, John T.; Newth, Christopher J.; Carcillo, Joseph A.; McQuillen, Patrick S.; Harrison, Rick E.; et al.
Abstract: Aim: In-hospital cardiac arrest occurs in >5000 children each year in the US and almost half will not survive to discharge. Animal data demonstrate that an immediate post-resuscitation burst of hypertension is associated with improved survival. We aimed to determine if systolic and diastolic invasive arterial blood pressures immediately (0–20 min) after return of spontaneous circulation (ROSC) are associated with survival and neurologic outcomes at hospital discharge. Methods: This is a secondary analysis of the Pediatric Intensive Care Quality of CPR (PICqCPR) study of invasively measured blood pressures during intensive care unit CPR. Patients were eligible if they achieved ROSC and had at least one invasively measured blood pressure within the first 20 min following ROSC. Post-ROSC blood pressures were normalized for age, sex and height. "Immediate hypertension" was defined as at least one systolic or diastolic blood pressure >90th percentile. The primary outcome was survival to hospital discharge. Results: Of 102 children, 70 (68.6%) had at least one episode of immediate post-CPR diastolic hypertension. After controlling for pre-existing hypotension, duration of CPR, calcium administration, and first documented rhythm, patients with immediate post-CPR diastolic hypertension were more likely to survive to hospital discharge (79.3% vs. 54.5%; adjusted OR = 2.93; 95%CI, 1.16–7.69). Conclusions: In this post hoc secondary analysis of the PICqCPR study, 68.6% of subjects had diastolic hypertension within 20 min of ROSC. Immediate post-ROSC hypertension was associated with increased odds of survival to discharge, even after adjusting for covariates of interest.